Pengaruh Pendapatan Operasional dan Biaya Operasional Terhadap Laba pada Perusahaan Farmasi yang Terdaftar di BEI Periode 2018-2021 - Septiawan, Erid Habibillah; Teti Chandrayanti; Meri Dwi Anggraini (Fakultas Ekonomi, Universitas Ekasaktii, 2023)
The purpose of this study is to examine how operating income and operating costs affect profits in pharmaceutical companies listed on the IDX from 2018 to 2021. Multiple Linear Regression Models are used to analyze the data, which comes from secondary information found in the company's income statement. Ten pharmaceutical companies listed on the Indonesia Stock Exchange from 2018 to 2021 became the population of this study, with eight companies as samples. The results of the hypothesis show that partially the operating income variable (X1) has an effect and is significant on earnings where the value of t hit > t table ( 6.961>1.669) while Operational Costs (X2) have no effect and are significant on profit where the value of t hit > t table (1.815>1.669) with sig (0.08>0.05), while simultaneously operating income and operating costs on Profit (Y) where value F Hit > F table (1625.551>3.33). with an adjusted R2 test value of 0.991, it means that 99.1 % of profit is influenced by operating income and operating costs while the remaining 0.8% is influenced by other variables that are not examined in this study.